Urological Injuries during Colorectal Surgery - Ferrara, Marco; Kann, Brian R. (Clinics in Colon and Rectal Surgery, 2019)
The proximity of the colon and rectum to the organs of the urologic system virtually ensures that iatrogenic urologic injuries become a distinct possibility during complex colorectal surgical procedures. An intimate knowledge of urogenital anatomy as well as strategies for identification and repair of potential injuries is of paramount importance. Attention is mandated when operating within the narrow confines of the pelvis, as this is where these structures are most at risk. The ureters are at highest risk of injury, followed by the bladder and urethra. The nature of these injuries encompasses both functional and mechanical morbidities. Patient factors, including prior pelvic surgery, radiation, inflammatory bowel disease, infectious processes, and urogenital abnormalities all increase the risk of injury. As colorectal surgeons encounter an increasing number of patients with the above risk factors, it is important to be familiar with the various urologic injury patterns, their diagnosis, and appropriate management.
Keywords: iatrogenic injury; ureter; bladder; urethra; colorectal surgery